2022
DOI: 10.2147/opth.s382899
|View full text |Cite
|
Sign up to set email alerts
|

The UCI EyeMobile Preschool Vision Screening Program: Refractive Error and Amblyopia Results from the 2019–2020 School Year

Abstract: To introduce the University of California Irvine (UCI) EyeMobile for Children preschool vision screening program and describe the ophthalmic examination results of children who failed screening with the PlusoptiX S12C photoscreener during one school year. Patients and Methods: Children aged 30-72 months were screened with the PlusoptiX using ROC mode 3 during the 2019-2020 school year. Children who failed screening were referred for comprehensive eye examination on the EyeMobile mobile clinic. Presence of ambl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The earlier study details vision screening performed using the Plusoptix, which had a significantly lower exam referral rate of 10.4% (546/5226), while ours using the Retinomax had a rate of 28.0% (1425/5074). 17 The following is a comparison of refractive errors found during examination by the previous study and ours: emmetropia (27.1% vs 40.2%), hyperopia (42.5% vs 35.4%), myopia (30.4% vs 24.4%), and astigmatism (81.3% vs 71.8%). Our study found higher emmetropia and lower rates of refractive errors, likely due to the higher sensitivity of the Retinomax, with a tendency to over-refer for exams as shown by a recent comparative study of both devices.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The earlier study details vision screening performed using the Plusoptix, which had a significantly lower exam referral rate of 10.4% (546/5226), while ours using the Retinomax had a rate of 28.0% (1425/5074). 17 The following is a comparison of refractive errors found during examination by the previous study and ours: emmetropia (27.1% vs 40.2%), hyperopia (42.5% vs 35.4%), myopia (30.4% vs 24.4%), and astigmatism (81.3% vs 71.8%). Our study found higher emmetropia and lower rates of refractive errors, likely due to the higher sensitivity of the Retinomax, with a tendency to over-refer for exams as shown by a recent comparative study of both devices.…”
Section: Discussionmentioning
confidence: 75%
“…Notably, the rate of no-show (28.1%) was improved from the initial study (36.9%) analyzing the 2019–2020 school year. 17 The remarkably low number of strabismic amblyopic subjects might be influenced by initial screening based principally on refraction, using the Retinomax device; therefore to better screen for strabismus, a recently developed and studied device, the Blinq vision scan with capabilities to detect even micro-strabismus, could be incorporated into our screening protocol. 40 Staff will also be trained and equipped to evaluate and screen for strabismus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation